Postheparin plasma diamine oxidase values in the follow up of patients with small bowel Crohn's disease. Issue 8 (August 1991) - D'Agostino, L; Pignata, S; Daniele, B; Visconti, M; Ferraro, C; D'Adamo, G; Tritto, G; Ambrogio, G; Mazzacca, G
Abstract : Measurement of postheparin plasma diamine oxidase (PHD) activity has been proposed to assess mucosal integrity in several diseases of the small intestine. In Crohn's disease, PHD values identify a group of patients with predominantly small bowel mucosal damage. To determine the role of mucosal involvement in the progression of small bowel Crohn's disease and whether different PHD values can predict different outcomes the changes in PHD values in 41 patients with small bowel Crohn's disease admitted consecutively to our department were investigated. The test was performed during periods of active disease and after either medical or surgical treatment had resulted in improvement. PHD values were significantly lower than in normal subjects (normal range 3.7-7.7 U/ml). In 35 patients with active disease (Crohn's disease activity index (CDAI) greater than 150) two groups were identified by choosing a cut off value of 2 U/ml: 93% of the 15 patients with PHD values lower than 2 U/ml (mean (SD) 1.36 (0.46) U/ml) relapsed at least once in the following year, while only the 20% of the 20 whose values were higher than 2 U/ml (mean (SD) 3.69 (1.50)) relapsed in the same period. The data were statistically significant (Yates's corrected chi 2 = 15.63; p less than 0.0001). The positive and negative predictive values of the test were 93% and 80%, respectively. During relapses, PHD values were consistently lower than previous values, and increased significantly after effective medical or surgical treatment. In the six patients in whom there were no changes in disease activity (CDAI persistently less than 150), there was no change in PHD values. This test may be useful for identifying Crohn's disease patients who are likely to relapse. Furthermore, the data indicate that mucosal damage is common in active small bowel Crohn's disease and improves at least in part after treatment.